Identifying Risk and Protective Factors for Shoulder Pain in Competitive Swimmers: The Role of Stroke Specialty and Competitive Level - Diogo Nunes Sousa; Eduardo Santos; Rui Escaleira; Daniel Moedas; Bárbara Campos; Eduardo Malavolta; Hélder Pereira; Nuno Sevivas (The Hive)
Background: Competitive swimmers are frequently exposed to overuse injuries. The etiology of overuse injuries is not fully understood but has been associated with training volume and biomechanical/anatomical characteristics of each swimmer.